Psychometric Properties of the 19-Item Audit of Diabetes Dependent Quality of Life (ADDQoL-19) Questionnaire in Adults with Uncontrolled Type 2 Diabetes Mellitus in Eket, Nigeria - Donatus Onyeka Adigom; Imo Emmanuel Udoh; Mary Richard Akpan (American Journal of Biomedicine and Pharmacy, 2026)
Purpose: We undertook to assess the validity and reliability of the 19-Item Audit of Diabetes Dependent Quality of Life (ADDQoL-19) questionnaire in patients with uncontrolled type 2 diabetes mellitus (T2DM) in Eket, South-South Nigeria. Methods: A total of 153 patients were recruited from the outpatient clinics of two secondary and two primary healthcare facilities in Eket between February and September, 2025. The ADDQoL-19 questionnaire was administered to each patient through self-administration method. Exploratory factor analysis was conducted with Varimax rotation. Reliability analysis was performed using Cronbach’s alpha (α) coefficient of internal consistency reliability. Results: 62.7% of patients were females. The mean age, HBA1c, weight, and BMI of the participants were 50 ± 15 years, 7.9 ± 1.5%, 60.8 ± 12.3 Kg and 23.83 ± 5.74 Kg/m2 respectively. Cronbach’s alpha coefficient was 0.857. Exploratory factor analysis identified 5 components with eigenvalues greater than 1. A total of 16 domains of ADDQoL-19 loaded highly (> 0.40) on a single factor using a forced one-factor solution (range from 0.457 to 0.698). Conclusion: The ADDQoL-19 questionnaire maintained its original psychometric properties and achieved adequate reliability and validity. It is therefore suitable in determining quality of life (QoL) among patients with uncontrolled T2DM in the study population.